Investigation of an oncolytic herpes simplex virus as a potential therapeutic agent for gastroenteropancreatic neuroendocrine neoplasms - Colin H. Quinn; Janet R. Julson; Michael H. Erwin; Hooper R. Markert; Larua V. Bownes; Jerry E. Stewart; Sorina Shirley; Karina J. Yoon; Jamie M. Aye; James M. Markert; Elizabeth A. Beierle (Scientific Reports)
Abstract Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) present unique challenges due to their heterogeneity and limited treatment options. Oncolytic virotherapy has emerged as a promising therapeutic for other NETs and thus, we sought to investigate the potential of an engineered oncolytic herpes simplex virus (oHSV), M002, for GEP-NETS. We employed an established long-term passage GEP-NET cell line and a unique, human pediatric patient-derived xenograft GEP-NET line. We found the virus to effectively infect, replicate within, and kill both cell lines in vitro. Similar effects were noted in vivo, with M002 decreasing tumor growth and improving overall survival in mice bearing tumors from both the established cell line and human GEP-NET PDX. Overall, these studies provide an evaluation of an oncolytic HSV in GEP-NETs, highlighting its therapeutic potential and considerations for clinical translation.